2013
DOI: 10.1590/s1519-69842013000200025
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects of Eriopis connexa (Germar) (Coleoptera: Coccinellidae) fed on different insect pests of maize (Zea mays L.) and sorghum [Sorghum bicolor L. (Moench.)]

Abstract: Eriopis connexa (Germar) (Coleoptera: Coccinellidae) occurs in several countries of South America and its mass rearing is important for biological control programmes. This work evaluated biological aspects of E. connexa larva fed on eggs of Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) and Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) frozen for one day, fresh eggs of Diatraea saccharalis (Fabricius) (Lepidoptera: Pyralidae), S. frugiperda newly-hatched caterpillars, nymphs of Rhopalosip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
6
0
3
Order By: Relevance
“…The development time (days) was 14.8 and 14.9 days in treated and control groups, respectively. Silva et al (2013) found a total development period of 12.6±0.2 and 14.4±0.2 days for treatment fed different aphids as prey, which is consistent with our study. However, significant differences were observed in development time in stages L1, L4 and pupae between treated and control groups.…”
Section: Discussionsupporting
confidence: 93%
“…The development time (days) was 14.8 and 14.9 days in treated and control groups, respectively. Silva et al (2013) found a total development period of 12.6±0.2 and 14.4±0.2 days for treatment fed different aphids as prey, which is consistent with our study. However, significant differences were observed in development time in stages L1, L4 and pupae between treated and control groups.…”
Section: Discussionsupporting
confidence: 93%
“…foi a mais numerosa, provavelmente devido à variedade de presas. A polifagia de Eriopis connexa foi relatada por Silva et al (2013) sugerindo que essa espécie pode se alimentar de um grande número de pragas de milho e sorgo, e que a disponibilidade e qualidade de alimentos são fundamentais para estabelecimento da espécie em uma nova área.…”
Section: Resultsunclassified
“…Mass rearing and release of predatory insects in agricultural and forest areas for biological control programs (Tavares et al 2012;Naranjo et al 2015) is dependent on the ecology and biology of a pest species and its associated predator guild (Sørensen et al 2012;Silva et al 2013, Grayson et al 2015. Determination of effective predators for suppression of targeted prey represent the first step for applied biological control programs (De Clercq & Degheele 1997).…”
mentioning
confidence: 99%